Detailed characterization of the Ti-O based thin films obtained by cathodic arc evaporation - Vukoman Jokanović; Nenad Bundaleski; Božana Čolović; Manuela Ferarra; Bojan Jokanović; Ilija Nasov (Zaštita Materijala)
Physicochemical properties of thin films on the base of titanium oxides, obtained by a cathodic arc evaporation on the surface of glass substrate are analysed in details. The analysis of these films was made by using XRD, FTIR, SEM, XPS analysis and ellipsometry. On the basis of these analyses, particularly analysis obtained by XPS, the oxidative state Ti and corresponding phases are determined through various film layers from the surface to the substrate. The depth of the various levels and their extinction coefficients and refractory indexes are estimated by ellipsometry.